GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG GEJALA KANKER LEHER RAHIM - Fatin Izzati; R. Sri Rezeki (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Cervical cancer is a cancer that attacks the lower end of the uterus that protrudes into the vagina, is generally invisible, but can be felt by the sufferer. The early stages of uterine cancer begin with gradual cell mutation, but are progressive and eventually develop into carcinoma. Cervical cancer can spread through blood vessels, lymph vessels, or directly to other vital organs. Until now, cervical cancer is still the first disease that most often attacks women in Indonesia. The purpose of this study was to determine the extent of knowledge of young women about the symptoms of cervical cancer. This type of research is a descriptive survey and the design of this study is cross-sectional. The population is 41 students and the sample obtained is 19 women, the sampling technique uses purposive sampling. Based on the results of the study on the knowledge of young women about the symptoms of cervical cancer, the results obtained were with a score of 3.422 (34.22%), it can be concluded that the knowledge of young women about the symptoms of cervical cancer is categorized as "not good". It is recommended for young women to further explore knowledge about the symptoms of cervical cancer so that it can be detected early, and it is hoped that young women should seek more information about the symptoms of uterine cancer to increase knowledge about the symptoms of cervical cancer.